2016
DOI: 10.1186/s12879-016-2050-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of colonization by methicillin-resistant Staphylococcus aureus ST398 in pigs and pig farm workers in an area of Catalonia, Spain

Abstract: BackgroundA livestock-associated clonal lineage (ST398) of methicillin-resistant Staphylococcus aureus (MRSA) has been identified causing colonization or infection in farm workers. The aim of the study was to analyze the prevalence of MRSA-ST398 colonization in pigs and in pig farmers in an area with a high pig population (Osona, Barcelona province, Catalonia, Spain).MethodsWe performed a cross-sectional prevalence study in Osona (Catalonia, Spain), from June 2014 to June 2015. All pig farm workers from 83 far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 41 publications
7
37
0
1
Order By: Relevance
“…We also analysed the antibiotic resistance phenotypes in MRSA of the different groups; we detected greater resistance to erythromycin and especially to clindamycin in MRSA-Tet R strains. A similar resistance profile was identified in a previous study on pig farm workers [6] and could be associated with the enrichment in clindamycin resistance genes (specially lnuA, lunB and vga) among MRSA CC398 isolates [5].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We also analysed the antibiotic resistance phenotypes in MRSA of the different groups; we detected greater resistance to erythromycin and especially to clindamycin in MRSA-Tet R strains. A similar resistance profile was identified in a previous study on pig farm workers [6] and could be associated with the enrichment in clindamycin resistance genes (specially lnuA, lunB and vga) among MRSA CC398 isolates [5].…”
Section: Discussionsupporting
confidence: 78%
“…The county of Osona (Barcelona, Catalonia, Spain) is an area with a high density of pig farms. Furthermore, a high nasal carriage rate of MRSA ST 398 (all Tet R ) has been recently detected in pig farm workers and farm animals in the Osona region [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all farms were MRSA-positive, but samples from Farms B and D showed considerably lower concentrations on MRSA-agar than on SA-agar. A large fraction of the pig farms, for example in Denmark ( Ministry of Environment and Food of Denmark, 2017 ), Germany ( Dahms et al , 2014 ), Spain ( Reynaga et al , 2016 ), and Poland ( Mroczkowska et al , 2017 ) are MRSA-positive, and the fraction has increased over time. The results of this study are therefore also relevant for other countries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, S. aureus carriage rate was significant high in India (71.4%) and Ireland (26%–73%), 32 , 33 and MRSA carriage rate was significant high in Germany (49%–70.8%) and Spain (46%). 34 , 35 There may be several reasons for this difference, such as geographical location, sampling methods, bacterial isolation and identification methods (conventional biochemical methods or PCR test; enrichment or no enrichment), livestock density, and antibiotic usage. In this study, S. aureus (including MDRSA) prevalence rate in slaughterhouse pigs was significantly higher than that observed in farm pigs.…”
Section: Discussionmentioning
confidence: 99%